Speciation of Phosphorus from Agricultural Muck Soils to Stream and Lake Sediments. Issue 4 (1st July 2018) - Audette, Yuki; O'Halloran, Ivan P.; Nowell, Peter M.; Dyer, Richard; Kelly, Ross; Voroney, R. Paul
Abstract : The nature and management of agricultural soils can influence the forms of legacy P present in affected sediments; however, few studies have specifically characterized P in sediments affected by polder agriculture. In this study, the speciation of P as it flows from the muck soils of the Holland Marsh to the sediments of the West Holland River and Lake Simcoe, Ontario, Canada, was investigated. The distribution of P fractions and the characterization of organic P were analyzed by the sequential fractionation method and solution 31 P nuclear magnetic resonance spectroscopy, respectively. Organic P was the predominant P form (∼58% of total P) in muck soils, whereas the redox‐sensitive P fraction was predominant in surface stream sediments rich in organic matter (∼41–48% of total P), despite these sediments exhibiting near‐neutral pH and high concentrations of both Ca and P. The proportion of relatively recalcitrant organic P forms was much greater in the muck soils than that exhibited by both stream and lake sediments. The decreasing proportion of recalcitrant organic P forms in sediments downstream from the Holland Marsh indicated the potential for faster organic P cycling. Our findings support the notion that diesters and pyrophosphate should be monitored, in addition to loosely bound inorganic P, due to their potential impact on water quality. The unique environment of the streams and lake area is considered to be particularly vulnerable to excessive fertilizer P use in adjacent croplands. Core Ideas: The predominant P fraction in muck soil was recalcitrant organic P. The predominant P fraction in organic matter‐rich sediments was redox‐sensitive P. The predominant form of organic P in sediments was labile orthophosphate diesters. Organic P cycles faster in stream sediments than that in muck soils.